From the pine tree, learn of the pine tree; from the bamboo, learn of the bamboo (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Pa is in Florianópolis, A. in São Paulo. Both decide to write an academic paper about dance dramaturgy. Pa.'s students are confused. What exactly does it mean to be a dramaturgist? Pa. answers that dramaturgy is a practice. Pa. tells A. that she conducted some dramaturgical practices with her students, but it went wrong. In class, students either gave orders, tips, or said whether they like it or not. That led A. to come up with an idea for the title of the paper: Order, tip or taste? The deviations and misconceptions of the work of dramaturgists. Pa. is more interested in the first answer she gave to her students: dramaturgy is a practice. Pa. and A. decide that this paper would be the outcome of a remote practice in which A. and Pa. would be artists and dramaturgists of each other.
Keywords: dance dramaturgy; dance process; dramaturgical practice; dramaturgical tools